PENERAPAN PRATIKUM IPA PADA MATERI PERKEMBANGBIAKAN TUMBUHAN UNTUK MENINGKATKAN HASIL BELAJAR IPA PADA SISWA KELAS IV DI UPTD SDI NGORAMAWO - Paba, Maria Skolastika; Lawe, Yosefina Uge; Dolo, Fransiskus Xaverius; Kua, Maria Yuliana (Jurnal Dedikasi Pendidikan, 2025)
TThe purpose of this research is to improve science learning outcomes and improve the learning process by modifying the learning pattern that has so far only been monotonous for teachers so that it becomes independent learning based on student initiatives using the practicum method in class IV on grafting material. The research technique used is Classroom Action Research (CAR), with the research subjects being 14 class IV students of UPTD SDI Ngoramawo. The data collection tool uses tests, with analysis techniques using interactive analysis techniques. The results of this classroom action research can be concluded that learning science on the material of Plant Propagation, especially in grafting using the practicum method in class IV can improve student learning outcomes and can improve the learning process, this is evidenced by the results of student learning outcomes, it can be seen that the average acquisition value in cycle 1 is 50.71 then in cycle 2 increased to 85